Lycocasuarines A–C, Lycopodium alkaloids from Lycopodiastrum casuarinoides. Issue 52 (27th December 2017) - Wang, Lu-Lu; Zhou, Zhong-Bo; Zhu, Xin-Liu; Yuan, Fang-Yu; Miyamoto, Tomofumi; Pan, Ke
Graphical abstract: Highlights: Three new lycodine-type Lycopodium alkaloids were isolated from Lycopodiastrum casuarinoides. Lycocasuarine A (1 ) possesses a rearranged five-membered ring D resulting from C-8/C-15 cleavage and a new C-7/C-15 linkage. Lycocasuarine B (2 ) is the first Lycopodium alkaloid found to bear an additional carbon (C-17) directly bonded to C-8. Lycocasuarine C (3 ) showed inhibitory activity against acetylcholinesterase. Abstract: Three lycodine-type Lycopodium alkaloids (1 –3 ) were isolated from Lycopodiastrum casuarinoides . Their structures were elucidated by spectroscopic analysis, single-crystal X-ray crystallography, and computational methods. Compound1 possesses a rearranged five-membered ring D resulting from C-8/C-15 cleavage and a new C-7/C-15 linkage. Compound2 is the first Lycopodium alkaloid found to bear an additional carbon (C-17) directly bonded to C-8, which is particularly unusual from a biogenetic point of view. Compounds1 –3 were evaluated for acetylcholinesterase inhibitory activities.